The Influence of Financial Knowledge, Financial Attitude, and Financial Inclusion on Financial Management Behavior Among F&B MSME Actors in Pontianak - Rangga Adrianur; Edy Suryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of financial knowledge, financial attitude, and financial inclusion on financial management behavior among F&B MSME actors in Pontianak City. The research employs a quantitative associative method involving 150 respondents, with data analyzed using multiple linear regression in SPSS 25. The results show that the model is significant (F = 341.453; Sig. 0.000) with a strong relationship (R = 0.936) and high explanatory power (R² = 0.875). Partially, financial knowledge (t = 7.365; Sig. 0.000) and financial inclusion (t = 4.413; Sig. 0.000) have a positive and significant effect on financial management behavior, while financial attitude has no significant effect (t = 0.447; Sig. 0.642). In conclusion, enhancing financial literacy and access to financial services can improve the financial behavior of MSME owners. Future research is recommended to include additional variables such as self-control or social norms, expand the study to other sectors or regions, and adopt a longitudinal design to capture behavioral dynamics over time.